2007
DOI: 10.1002/adma.200602813
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Silica Formation: Effect of Block Copolypeptide Chemistry and Solution Conditions on Silica Nanostructure

Abstract: Developing new technologies as a consequence of controlling structure, chemistry, and functionality at the nanometer length scale is the ultimate goal of nanotechnology. One route to this goal is to draw lessons from nature, which has developed the ability to fabricate inorganic and inorganic-hybrid materials such as silica diatoms and nacre that have properties that the materials science community can only aspire to achieve. [1][2][3][4][5][6][7] The development of so-called biomimetic or bioinspired synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 37 publications
(28 reference statements)
1
71
0
Order By: Relevance
“…For example, peptides and proteins have recently been found as molecular templates for the synthesis of metal nanoparticles [2][3][4][5][6][7][8][9]. In addition, several studies have demonstrated that amine-containing macromolecules can mediate the formation of nanoscale silicas at ambient conditions [10][11][12][13][14][15][16][17][18][19]. Given the enormous interest in the synthesis and assembly of nanomaterials, this is an area that will continuously receive growing attention.…”
Section: Introductionmentioning
confidence: 98%
“…For example, peptides and proteins have recently been found as molecular templates for the synthesis of metal nanoparticles [2][3][4][5][6][7][8][9]. In addition, several studies have demonstrated that amine-containing macromolecules can mediate the formation of nanoscale silicas at ambient conditions [10][11][12][13][14][15][16][17][18][19]. Given the enormous interest in the synthesis and assembly of nanomaterials, this is an area that will continuously receive growing attention.…”
Section: Introductionmentioning
confidence: 98%
“…[27][28][29] Therefore, it becomes an investigation hotspot to clarify the biomineralization mechanism, which may provide a new paradigm for the environmentally benign synthesis of advanced materials at the molecular level. [30][31][32] Biosilica is the first studied biomaterials, which is produced by diatoms, radiolarians, and sponges with exquisite structure that exceeds human engineering capabilities. [32][33][34][35] It was found that silicateins and silaffins, the biomolecules involved in the biomineralization of sponge silica spicules were able to induce the in vitro formation of silica and other nonbiological inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] To date, however, this approach has been limited to the synthetic modification of the nanoparticle to directly interact with inner recognition sites of some animal proteins. An alternative strategy would be to target the surface of a rich plant seed protein through complementary interactions, using the shape and physical characteristics of the protein to dictate the structural features in the resulting nanoparticles and protein composites.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these, such as bones, teeth, and shells, utilize crystalline minerals like calcium carbonate and hydroxyapatite (HAp) to stiffen and strengthen the tissue. [1][2][3][4][5] These mineral crystals are often arranged in ordered arrays and unique shapes. In biological mineralized tissues, almost all mineralized tissues composed of a distinctive assembly of acidic proteins, glycoproteins, silicatein, collagen, and ferritin cause the deposition of inorganic matter inside or around the cell where the nucleation and growth of these materials is controlled.…”
Section: Introductionmentioning
confidence: 99%